Interaction between GPR110 (ADGRF1) and tight junction protein occludin implicated in blood-brain barrier permeability - Bill X. Huang; Huazhen Chen; Yuyoung Joo; Heung-Sun Kwon; Cheng Fu; Arthur A. Spector; Hee-Yong Kim (iScience, 2023)
Summary: Activation of adhesion receptor GPR110 by the endogenous ligand synaptamide promotes neurogenesis, neurite growth, and synaptogenesis in developing brains through cAMP signal transduction. However, interacting partners of GPR110 and their involvement in cellular function remain unclear. Here, we demonstrate using chemical crosslinking, affinity purification, and quantitative mass spectrometry that GPR110 interacts with the tight junction adhesion protein occludin. By removing non-specific partners by comparing the binding proteins of GPR110 WT and an inactive mutant exhibiting impaired surface expression, occludin was distinguished as a true binding partner which was further confirmed by reciprocal co-immunoprecipitation assay. Deletion of GPR110 in mice led to the disruption of blood-brain barrier (BBB) and reduced occludin phosphorylation at Y285 in the brain. The Y285 phosphorylation increased upon the ligand-induced activation of GPR110. These data suggest an important role of GPR110-occludin interaction in BBB function and association of previously unknown GPR110-dependent occludin phosphorylation at Y285 with BBB integrity.